2012
DOI: 10.2225/vol15-issue3-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa: An in vivo system to study possible survival strategies within citrus xylem vessels based on global gene expression analysis

Abstract: Xylella fastidiosa inhabits the plant xylem, a nutrient-poor environment, so that mechanisms to sense and respond to adverse environmental conditions are extremely important for bacterial survival in the plant host. Although the complete genome sequences of different Xylella strains have been determined, little is known about stress responses and gene regulation in these organisms. In this work, a DNA microarray was constructed containing 2,600 ORFs identified in the genome sequencing project of Xylella fastid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In fact, oxyR mutants were impaired in their ability to attach to surfaces, to aggregate with other cells, and to consequently form biofilm. Thus, biofilm formation by X. fastidiosa might be an adaptive response to the exogenous oxidative stress normally encountered by the bacterium in the xylem vessels [54][55][56][57]. In line with the previous considerations, it seems likely that the non-lethal concentration of 500 µM NAC increases the levels of ROS, providing the selective pressure for hyper-biofilm-forming phenotypes.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In fact, oxyR mutants were impaired in their ability to attach to surfaces, to aggregate with other cells, and to consequently form biofilm. Thus, biofilm formation by X. fastidiosa might be an adaptive response to the exogenous oxidative stress normally encountered by the bacterium in the xylem vessels [54][55][56][57]. In line with the previous considerations, it seems likely that the non-lethal concentration of 500 µM NAC increases the levels of ROS, providing the selective pressure for hyper-biofilm-forming phenotypes.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, NAC can react with free radicals and become a thiyl radical itself [52,53]. In X. fastidiosa, ROS acted as an environmental cue that stimulated biofilm development during the early stage of plant colonization, such that the oxidative imbalance was actually required by X. fastidiosa to achieve maximum xylem colonization [54]. It has also been proved that X. fastidiosa biofilm is related to the sensing of a redox imbalance via the oxidative stress regulator OxyR [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression profiling of Xf, together with genomic comparisons and mutagenesis (see Section 2.5), clarified the genetic basis and mechanisms of colonization and pathogenicity, although several processes remain elusive largely due to uncharacterized or nonexclusive genetic elements [17,56,106]. Hybridization-based microarray, quantitative PCR (qPCR) and RNAseq studies revealed that differences in genomic sequences between strains are reflected and amplified in gene expression, with a conserved core gene pool linked to survival in plant xylem and a flexible set including genes that favors adaptation in different hosts and putative pathogenicity factors: Xf plastically adapts its survival strategy to the environment [111,[148][149][150][151][152]. They also showed that plasmids and prophages are transcriptionally active and modulated independently from the rest of the genome [111,149].…”
Section: Gene Expression Profilesmentioning
confidence: 99%
“…It is well accepted that Ohr peroxidase activity enhances cells' resistance against organic hydroperoxides insult. Among the several bacteria that can express the ohr gene, some are very relevant in terms of public health and agriculture, including Pseudomonas aeruginosa, Xylella fastidiosa and Chromobacterium violaceum Chuchue et al, 2006;Federici et al, 2012;. There are evidences of the involvement of Ohr in bacterial virulence, although this is still a controversial issue.…”
Section: -Ohr and Virulencementioning
confidence: 99%